W.J. Thomas Mitchell, Picture Theory : Essays on verbal and Visual Representation - Klucinskas, Jean (Études littéraires)

(untitled) (Département des littératures de l'Université Laval, 1996)
W. J. Thomas Mitchell, Picture Theory : Essays on Verbal and Visual Representation.